PENGARUH WORK FAMILY CONFLICT DAN BEBAN KERJA TERHADAP WORK LIFE BALANCE DENGAN STRESS KERJA SEBAGAI MEDIASI (STUDI PADA PERAWAT WANITA RUMAH SAKIT BADAN LAYANAN UMUM DAERAH PATUT PATUH PATJU LOMBOK BARAT) - Fatmia Jaya, Septina; Suryatni, Mukmin; Buana Sakti, Dwi Putra (Jurnal Magister Manajemen, 2023)
This study was conducted to examine the effect of Work Family Conflict and Workload on Work Life Balance with Work Stress as Mediation in Female Nurses at the Patut Patuh Regional General Hospital, West Lombok. the type of research used is causal associative research, namely research that examines the relationship of one or more variables to other variables. This study focused on female nurses at the Patut Patju Regional General Hospital, West Lombok. Meanwhile, there are 71 female nurses who have toddlers at the Patut Patuh Patju Regional General Hospital, West Lombok. In this study, the 71 nurses will be used as research respondents. Data Analysis Procedure with Partial Least Square (PLS) Analysis. The results of this study show that Work Family Conflict has no significant effect on Work Life Balance. Workload has no significant effect on Work Life Balance. Work Family Conflict has a positive and significant effect on Work Stress. Workload has a positive and significant effect on work stress. Work Stress has a negative but not significant effect on Work Life Balance. Work Family Conflict has no significant negative effect on Work Life Balance through Work Stress. Work Stress is unable to mediate the effect of workload on Work Life Balance.